Estrategia didáctica para la utilización de blog educativos en el desempeño docente de los maestros de la asignatura estudios sociales y su didáctica. - Arce Sanmartín, Gladys Magdalena (2015)
Internet offers a wealth of opportunities all to optimize the teaching-learning process . Despite being associated with its usual intimate and everyday nature , the blog is a large potential resource when working collaboratively in the classroom or outside content preferably transverse and core competencies. In short, the weblog allows a range of shared experiences that allow students to reflection and contrast own and others' ideas. That's why the aim of this work is to use the educational blog on the teaching performance of teachers of social studies subject .